Eisenstein, Montage and 'filmic writing' - Quigley, Paula (Brill, 2004)
This essay considers the ways in which Eisenstein’s interest in the ideogram as a model for film language was reconsidered and reconfigured in the work of the French film theorist Marie-Claire Ropars-Wuilleumier in the 1980s. It argues that in this process, Eisenstein’s emphasis on the emotional and visceral impact of the film image was lost in favour of the textual emphasis characteristic of film theory at this time.
The Montage Principle: Eisenstein in New Critical and Cultural Contexts